CATOSTYLUS OUWENSI (RHIZOSTOMEAE, CATOSTYLIDAE), A NEW JELLYFISH FROM IRIAN (NEW GUINEA) AND OUWENSIA CATOSTYLI n, gen., n, sp., PARASITIC IN C.OUWENSI - SITI HADIDJAH MOESTAFA; BAYARD H MCCONNAUGHEY (BRIN Publishing (Penerbit BRIN), 1966)
-